Tindak Tutur Ilokusi Direktif dalam Novel Nonik Jamu Karya Rina Suryakusuma - Reni Agustina; Sarwiji Suwandi (CV. Alim's Publishing, 2026)
The study of illocutionary speech acts is not limited to spoken interactions but also extends to written forms, including dialogues and narratives in literary works such as novels. Rina Suryakusuma’s novel Nonik Jamu contains numerous directive illocutionary speech acts uttered by its characters, aimed at encouraging the interlocutors to perform spesific actions. This study aims to describe the directive illocutionary speech acts in the novel Nonik Jamu by Rina Suryakusuma. This research employs a qualitative descriptive approach. The data consist of sentences containing directive illocutication of speech acts within the novel, which were analyzed using Searle’s classification.The data source used in this study written document in the form of the novel. The sampling technique was conducted through purposive sampling. The data validity testing technique used was source triangulation, while the data analysis technique was the flow analysis model. Based on the result of the data analysis, the directive illocutionary speech acts found in this study include commanding, forbidding, requesting, suggesting, inivting, and entreating. The most dominant form of directive speech act identified in this study is commanding. This research is expected to broaden insights in the field of linguistics, particularly regarding the concept and proper application of speech acts in communication.